Nomads and settlers in the research-technology regime: The case of transmission electron microscopy. (September 2017) - Lettkemann, Eric
This article presents historical evidence for the rise of a new type of research-technology community that deviates in several respects from the social and epistemic configurations of work that Terry Shinn described in his seminal writings on the origins of the research-technology regime. The more recent type of settlers is distinguished from a nomadic type, prevalent in Shinn's work. It is argued that, despite many configurational differences, both types constitute functional equivalents for producing and disseminating generic instrumentation. An important difference, however, is the prolonged life expectancy of settler communities, resulting in long-term upgrading cycles. On the basis of a case study on transmission electron microscopy in Germany, the article investigates social and epistemic conditions facilitating the emergence and permanent institutionalization of a settler community. It seems that material resistances, hindering nomadic research practices, as well as support from scientific/industrial elites have great impact on the formation of settler communities.